Clinical skills in undergraduate program and Curricular change – does it make a difference? - Naushaba Sadiq , Syeda Kauser Ali ,Lubna Meraj , Sadia Chaudhry , Fauzia Abdus Samad , Naushaba Sadiq , Syeda Kauser Ali ,Lubna Meraj , Sadia Chaudhry , Fauzia Abdus Samad (Journal of Rawalpindi Medical College, 2019)
Background Clinical Skills Laboratory (CSL) was established at Foundation University Medical College (FUMC) in year 2009 with the introduction of integrated modular teaching program. A structured integrated curriculum was introduced from the Class of year 2013 for learning of clinical skills at CSL. This study was conducted to evaluate the effect of introducing the new curriculum on student’s performance in CSL. Methods A comparative analytical study was conducted. The OSCE scores of group A (Class of year 2011) were compared with group B (Class of 2013). Data collection tool was institutional checklist. The OSCE stations were of General Physical Examination (GPE), history taking, systemic examination of Gastrointestinal tract and communication skills. Reliability of the scores was estimated through Cronbach α. Mean scores of the two groups were compared using the independent sample t test and Mann Whitney U-test. Chi-square test was used to compare variables (years, gender and educational background). Comparison of student scores at different components of OSCE using Analysis of Variance (ANOVA) was done. Results Reliability of scores was 0.65 for group B and 0.52 for group A. comparison of overall scores of the two groups reflected improved performance in the group B (p 0.001). Comparison of scores at different components of OSCE using ANOVA also reflected better performance of group B (p<0.01). OSCE scores of both the groups were also correlated for gender and educational background. No difference was found in the two groups on the basis of gender and educational background. Conclusion To enhance the value of clinical skills training and to make it more effective, skill lab curriculum must be structured and integrated within the undergraduate curriculum. Key words;Clinical skills laboratory, undergraduate integrated curriculum, clinical skills training